2021
DOI: 10.1186/s12870-021-03208-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of Catharanthus roseus RLK1-like kinases in Nicotiana benthamiana

Abstract: Background The Catharanthus roseus RLK1-like kinase (CrRLK1L) is a subfamily of the RLK gene family, and members are sensors of cell wall integrity and regulators of cell polarity growth. Recent studies have also shown that members of this subfamily are involved in plant immunity. Nicotiana benthamiana is a model plant widely used in the study of plant-pathogen interactions. However, the members of the NbCrRLK1L subfamily and their response to pathogens have not been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In plants, it was further reported that MRLK proteins plays an important role in plant growth [ 46 , 47 ], cell wall integrity [ 16 ], fertilization [ 48 ], hormone signal transduction [ 14 , 17 , 49 ], and immune and stress response [ 16 , 24 , 45 ]. The MRLK genes have been identified in the genomes of Arabidopsis [ 47 ], rice [ 18 , 19 , 47 ], cotton [ 50 ], tobacco [ 21 ], soybean [ 51 ], pear [ 52 ] and apple [ 53 ]. So far, however, there have been no reports on the members of this family in foxtail millet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, it was further reported that MRLK proteins plays an important role in plant growth [ 46 , 47 ], cell wall integrity [ 16 ], fertilization [ 48 ], hormone signal transduction [ 14 , 17 , 49 ], and immune and stress response [ 16 , 24 , 45 ]. The MRLK genes have been identified in the genomes of Arabidopsis [ 47 ], rice [ 18 , 19 , 47 ], cotton [ 50 ], tobacco [ 21 ], soybean [ 51 ], pear [ 52 ] and apple [ 53 ]. So far, however, there have been no reports on the members of this family in foxtail millet.…”
Section: Discussionmentioning
confidence: 99%
“…Up till now, 16 MRLK genes have been reported in the rice genome [ 18 ], but according to our recent study, at least 67 members were identified in this plant [ 19 ]. A total of 31 MRLK members that could take part in the response to biotic and abiotic stress have been characterized in the tobacco genome [ 20 , 21 ]; such overexpression of NtCrRLK1L47 could enhance salt tolerance in tobacco seedlings [ 20 ]. A total of 24 CrRLK1L members were investigated in tomatoes, and they may also be involved in the stress tolerance of tomato [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potato StCrRLK1Ls promoter region have a variety of cis-regulatory elements in response to plant hormones, defense and stress, and StCrRLK1Ls' expression has been altered after Phytophthora infestans infection, suggesting that they may play an important role in the response of potato to pathogenic fungi, and can be screened as candidate genes for further resistance research and functional analysis [47]. Upon Pseudomonas syringae infection, Nicotiana benthamiana NbCrRLK1Ls have displayed significant changes in expression, indicating that these genes may be involved in the response to Pseudomonas syringae [60]. Additionally, CqFER in Chenopodium quinoa, GmCrRLK1L20 in soybean, and NtCrRLK1L47 in tobacco have been documented to partake in the modulation of salt stress responses [42,46,61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous genome wide analysis of the CrRLK1L gene family has been carried out in various plant species, including Arabidopsis thaliana (L.), Oryza sativa L., Solanum lycopersicum, Nicotiana benthamiana , and Gossypium raimondii . The rice genome has 16, the tomato has 24, Nicotiana benthamiana has 31, and the diploid cotton species G. raimondii has 44 CrRLK1L genes ( Lindner et al., 2012 ; Nguyen et al., 2015 ; Niu et al., 2016 ; Rao et al., 2021 ; Ma et al., 2023 ). These studies prompted us to further research CrRLK1L gene families in wheat ( T. aestivum ) to unravel their role in plant growth, development, and stress responses.…”
Section: Introductionmentioning
confidence: 99%